2017
DOI: 10.1007/s00394-017-1539-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary l-methionine supplementation on intestinal integrity and oxidative status in intrauterine growth-retarded weanling piglets

Abstract: Methionine may have beneficial effects in improving intestinal integrity and oxidative status in IUGR weanling piglets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 51 publications
8
42
0
1
Order By: Relevance
“…The balance of cell apoptosis and proliferation are important for maintaining the turnover of the intestinal mucosal epithelium [55]. Inflammation and oxidative stress can induce excessive apoptosis and declined proliferation, which could lead to intestinal barrier dysfunction [56,57]. In the present study, we observed apoptosis was promoted in the intestinal mucosae of LPS-challenged broilers using a TUNEL assay.…”
Section: Discussionsupporting
confidence: 48%
“…The balance of cell apoptosis and proliferation are important for maintaining the turnover of the intestinal mucosal epithelium [55]. Inflammation and oxidative stress can induce excessive apoptosis and declined proliferation, which could lead to intestinal barrier dysfunction [56,57]. In the present study, we observed apoptosis was promoted in the intestinal mucosae of LPS-challenged broilers using a TUNEL assay.…”
Section: Discussionsupporting
confidence: 48%
“…The jejunum is not only the main place for the digestion and absorption of nutrients, but also the immune organ in the body [5]. Recent results have demonstrated that IUGR can cause jejunum damage in piglets at 21 and 50 days [6][7][8]. As for the IUGR programming consequences, IUGR might affect the jejunum function of growing pigs, such as immunization, intestinal barrier, proliferation, and apoptosis, but few relevant reports have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of IUGR on jejunum function is closely related to oxidative function. For example, previous research proved that imbalance of antioxidant homeostasis is an important factor contributing to intestinal mucosal injury induced by IUGR [8]. However, few effective methods to alleviate jejunum damage and oxidative stress in IUGR pigs have been found.…”
Section: Introductionmentioning
confidence: 99%
“…The VH (villus height), VW (villus weight) and CD (crypt depth) were measured by image‐pro plus software. The VSA (villus surface area) was calculated as follows (Su et al, ):VSA=π×VW2)(VM22+VH2…”
Section: Methodsmentioning
confidence: 99%
“…The intestine is a crucial organ essential for nutrient absorption and bile and waste excretion and an important site of host immunity (Chin, Hill, Aurora, & Spence, ). Adequate dietary Met is necessary for optimal protein synthesis and mucosal integrity, as well as the redox status in the small intestine in humans and animals (Chen et al, ; Su et al, ). A number of studies have demonstrated that Met deficiency suppresses protein synthesis and epithelial cell growth (Bauchart‐Thevret, Stoll, Chacko, & Burrin, ; Tang et al, ), and is relevant to overall health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%